1993
DOI: 10.1002/jmv.1890410205
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte responses and virus excretion as risk factors for intrauterine infection with cytomegalovirus

Abstract: Serological screening of pregnant women in this and a previous study identified 28 cases of primary infection with cytomegalovirus, 7 (25%) of whom transmitted the infection to their fetuses. Risk factors for intrauterine infection were: 1) age less than 20 years, 2) Caucasian rather than non-Caucasian race, 3) a weak response to cytomegalovirus antigen in the lymphocyte transformation test, and 4) the excretion of cytomegalovirus in the urine. The greatest risk was when a weak lymphoproliferative response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…Only a small percentage (1.2%) of CMV seropositive women in the present study were found to be shedding CMV compared to published data (46). Urinary shedding has a poor correlation with intrauterine infection, although it has been identified as a risk factor (15,42). In the present study one of the women from group B who seroconverted and was viremic at the time of testing was also shedding CMV in her urine and gave birth to a child with asymptomatic congenital CMV infection.…”
Section: Discussioncontrasting
confidence: 85%
“…Only a small percentage (1.2%) of CMV seropositive women in the present study were found to be shedding CMV compared to published data (46). Urinary shedding has a poor correlation with intrauterine infection, although it has been identified as a risk factor (15,42). In the present study one of the women from group B who seroconverted and was viremic at the time of testing was also shedding CMV in her urine and gave birth to a child with asymptomatic congenital CMV infection.…”
Section: Discussioncontrasting
confidence: 85%
“…In conclusion, these data cast some doubts on the value of some maternal factors, such as humoral and cellular immune response, as possible prognostic markers of intrauterine transmission, as postulated by some researchers (29,71,157,269). They should also be taken into consideration when testing the hypothesis that reinfection with a different HCMV strain may be responsible for the unfavorable outcome observed in some infants born to mothers with existing immunity (30).…”
Section: Congenital Infection In Twinsmentioning
confidence: 88%
“…Pre-and post-immunization guinea-pig sera with complementindependent neutralizing activity, specific for HCMV gB, were the generous gift of Dirk Gheysen (SmithKline Beecham). Acute and convalescent sera from pregnant women undergoing primary infection with HCMV (Fernando et al, 1993) were used in final dilutions of 1 : 100-1 : 500.…”
Section: Methodsmentioning
confidence: 99%